Plasma Levels of Soluble Receptor for Advanced Glycation End Products and Coronary Atherosclerosis: Possible Correlation with Clinical Presentation. Issue 3 (18th August 2013) - Falcone, Colomba; Bozzini, Sara; D'Angelo, Angela; Matrone, Benedetta; Colonna, Anna; Benzi, Alberto; Paganini, Edoardo Maria; Falcone, Rossana; Pelissero, Gabriele
Abstract : Receptor for Advanced Glycation End-products (RAGE) is a multi-ligand receptor ubiquitous present on epithelial, neuronal, vascular and inflammatory cells, usually expressed at low levels in homeostasis and to increased degrees at sites of stress or injury. The aim of the present study was to evaluate sRAGE plasma levels in patients with Acute Coronary Syndrome (ACS) and to assess its diagnostic efficacy in identification of patients with acute events. Plasma levels of sRAGE were determined in 860 patients with Coronary Artery Disease (CAD): 530 patients presented stable angina and 330 were observed during acute ischemic event (147 with unstable angina and 183 with myocardial infarction). sRAGE plasma levels were significantly lower in patients with ACS than in patients with stable angina: [median 584 pg/mL (IQR: 266–851 pg/mL) in MI patients, median 769 pg/mL (IQR: 394–987 pg/mL) in patients with unstable angina, median 834 pg/mL (IQR 630–1005 pg/mL) in patients with stable angina;P < 0.001 ]. sRAGE levels did not differ among ACS patients stratified by the extent of coronary artery disease. In conclusion, this study confirm the role of sRAGE in activation and progression of inflammatory process and suggests the possibility that sRAGE can be considered an indicator of destabilization of vulnerable plaque.